PEMIKIRAN MAHMUD YUNUS TENTANG HADIS ETIKA DAN KONTRIBUSINYA TERHADAP PERKEMBANGAN KAJIAN HADIS DI INDONESIA - M Zia Al-Ayyubi (IAIN Syekh Nurjati Cirebon, 2022)
This paper is a socio-historical study of Mahmud Yunus's contribution on hadithstudies in Indonesia, especially about ethical hadith. The study of hadith in Islamichistory actually began after Muhammad designation as messenger of God, AllahTa’ala. So at that time the transmission of the prophetic traditions is also started. Bythe times, Islam had been increasingly widespread, and it also has an impact on thedevelopment of hadith studies, riwaya as well as diraya. Shortly explained, hadithstudies also started to enter Indonesia and became important part of interests forIndonesian Moslem scholars to be disscused. One of them who paid much attentionand had high contributions on it is Mahmud Yunus. Since he wrote first book ofMusthalah Hadith in Indonesian language with his partner Mahmud Aziz, namely‘Ilm Musthalah Hadith. The discussion of Mahmud Yunus's thought on Hadithbecomes more interesting because of his experties is not on hadith. It was IslamicEducation. But once again, what Mahmud Yunus has contributed on history of thehadith studies development in Indonesia certainly cannot be underestimated